How to be Successful in the Interaction of Social Relations with Clients - Manfred, Doepp (British Journal of Healthcare and Medical Research, 2023)
Every client or patient hopes and expects to be positively received and uplifted by the therapist. If this is realized, success will result for both parties involved. Fortunately, it is possible to learn improved communication. The recommendations well suited for this are listed here, they result in a relationship of trust. This is especially important today, as many therapists and clients are uncertain as a result of the experience with infections and vaccinations. Reversing these tendencies is valuable.